Is Green Organizational Identity Related to Sustainability Performance? A Scooping Review - Agung DINARJITO; Nurmala AHMAR (International Journal of Environmental, Sustainability, and Social Science, 2023)
The abstract is made as a brief summary of the entire content of the article written Green Organizational Identity (GOI) needs to be implemented by companies to achieve sustainable corporate performance. As one of the intangible assets that can provide positive value to the company, GOI is believed to be able to improve the Sustainability Performance (SP) of the company. This research is qualitative research using scooping review to answer the research objectives. This study aims to identify the relationship between GOI and SP. The results of the study show that there is no research that has thoroughly discussed the relationship between GOI and SP. Existing research still partially discusses part of SP. GOI has an influence on environmental performance and its related derivative variables. This study contributes theoretically that GOI has a major influence on sustainable company performance, both directly and indirectly.